2023
DOI: 10.1111/nyas.15003
|View full text |Cite
|
Sign up to set email alerts
|

A neurocognitive theory of flexible emotion control: The role of the lateral frontal pole in emotion regulation

Abstract: Emotion regulation is essential to survive in a world full of challenges with rapidly changing contextual demands. The ability to flexibly shift between different emotional control strategies is critical to successfully deal with these demands. Recently, decision neuroscience has shown the importance of monitoring alternative control strategies.However, this insight has not been incorporated into current neurocognitive models of emotional control. Here, we integrate insights from decision and affective science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 149 publications
0
0
0
Order By: Relevance
“…Middle PFC activity was significantly higher in the prediction condition than in the trace condition of the PL pattern task. The middle PFC has been suggested to be associated with executive function switching [15]. In the PL pattern task of this study, the drawn figure and the next figure were different symbols.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Middle PFC activity was significantly higher in the prediction condition than in the trace condition of the PL pattern task. The middle PFC has been suggested to be associated with executive function switching [15]. In the PL pattern task of this study, the drawn figure and the next figure were different symbols.…”
Section: Discussionmentioning
confidence: 70%
“…Executive function is strongly associated with the PFC [7,8], and individual executive functions may be related to their area of localization within the PFC [9][10][11][12]. Previous studies have suggested that the right PFC is associated with inhibitory control of executive function [13,14] and that the middle PFC is associated with executive function switching [15]. A previous study that focused on tempo when Psych 2023, 5 writing letters showed a relationship with the right inferior parietal lobule [16].…”
Section: Introductionmentioning
confidence: 94%
“…One major challenge for future work will be to complement the existing self-report instruments for PAS with more objective, task-based measures. Another challenge will be to empirically compare and integrate PASTOR with theories emphasizing the role of flexible coping and emotion regulation for resilience (e.g., [53][54][55][56][57][58] ). From the perspective of PASTOR, regulatory flexibility may be one aspect of optimized stress response regulation and depend on PAS 12,14 .…”
Section: Discussionmentioning
confidence: 99%
“…(Koch et al, 2018)explains that strategies are needed to regulate emotions optimally in an unfamiliar environment. Emotional regulation is essential for someone to be able to live life; the ability to be flexible in regulating emotions shows the importance of someone having an emotional regulation strategy (Roelofs et al, 2023).…”
Section: Introductionmentioning
confidence: 99%